Factors Affecting Production Of Salted Anchovy Fish Preservation At Labuhan Maringgai Subdistrict East Lampung Regency - Sutarni Sutarni (Politeknik Negeri Lampung, 2013)
Development issues in the fisheries sub-sector is one of fishery products easily damaged and nonperishable, its implications need special handling and good processing of fish.To inhibit the growth of microorganisms that cause decaying in fish can be done two ways, namely the preservation of traditional and modern fishing. One of traditionally fish preservation is done by salting or often called stockfish. This study aims to analyze the production process and the factors that influence the production of salted anchovies fish agro- industry in labuhan Maringgai subdistrict East Lampung regency. The number of samples in this study were 30 respondents. The study was conducted from June to November 2012. Data was analyzed by descriptive qualitative and quantitatively by using multiple regression statistical analysis approach of cobb-douglas production function. The results of this research showed the production of salted anchovies were done traditionally, with the production of agro-processing stages include salted anchovies; sorting of raw materials, washing, boiling, draining, drying, sorting, packaging, and marketing. Resulted average production anchovies agro- industry reached 593.33 kg per period, the annual production capacity reaches 170 times. The factors that significantly affect the production of salted fish agro- industry is raw fish , sinks, deep soaking tubs, and a dummy use of ice, while the factors that did not significantly affect the production of salted anchovies agro- industry is salt, labor, and drying place.Elasticity value of Agro-industry productionof salted anchovies fish preservation in the research area is 1.006 which means Elasticity Production (EP> 1), indicating that the scale of agro economy salted anchovy fish preservation in condition increasing return to scale, the addition of the factors of production will lead to increase a greater production . Keywords: anchovies, production, processing, preservation, and agro-industry.